2007
DOI: 10.1348/026151006x118577
|View full text |Cite
|
Sign up to set email alerts
|

Trait emotional intelligence, psychological well‐being and peer‐rated social competence in adolescence

Abstract: The trait emotional intelligence (trait EI or trait emotional self‐efficacy) framework provides comprehensive coverage of emotion‐related self‐perceptions and dispositions. In this study, we investigated the relationship between trait EI and four distinct socioemotional criteria on a sample of Dutch adolescents (N = 282; 136 girls, 146 boys; mean age = 13.75 years). As hypothesized, trait EI was positively associated with adaptive coping styles and negatively associated with depressive thoughts and frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
204
2
23

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(254 citation statements)
references
References 37 publications
25
204
2
23
Order By: Relevance
“…Within educational settings, trait EI has been shown to relate to adaptive behaviors, such as higher attendance, and positive peer relations (Gugliandolo, et al, 2015;Ruttledge & Petrides, 2012;Mavroveli, Petrides, Sangareau & Furnham, 2009;Mavroveli, Petrides, Shove & Whitehead, 2008;Mavroveli, Petrides, Rieffe, & Bakker, 2007;Petrides, Sangareau, Furnham & Frederickson, 2006;Santeso, Reker, Schmidt & Segalowitz, 2006). Empirical evidence has also shown that trait EI has a positive effect on happiness, life satisfaction, affect (Platsidou, 2013;Chamorro-Premuzic, Furnham & Lewis, 2007;Petrides & Furnham, 2003), and academic success, primarily among at risk students (Mavroveli, Sanchez-Ruiz, 2010;Parker, Summerfeldt, Hogan & Majeski, 2004;.…”
Section: Trait Emotional Intelligence (Ei) and Educational Outcomesmentioning
confidence: 99%
“…Within educational settings, trait EI has been shown to relate to adaptive behaviors, such as higher attendance, and positive peer relations (Gugliandolo, et al, 2015;Ruttledge & Petrides, 2012;Mavroveli, Petrides, Sangareau & Furnham, 2009;Mavroveli, Petrides, Shove & Whitehead, 2008;Mavroveli, Petrides, Rieffe, & Bakker, 2007;Petrides, Sangareau, Furnham & Frederickson, 2006;Santeso, Reker, Schmidt & Segalowitz, 2006). Empirical evidence has also shown that trait EI has a positive effect on happiness, life satisfaction, affect (Platsidou, 2013;Chamorro-Premuzic, Furnham & Lewis, 2007;Petrides & Furnham, 2003), and academic success, primarily among at risk students (Mavroveli, Sanchez-Ruiz, 2010;Parker, Summerfeldt, Hogan & Majeski, 2004;.…”
Section: Trait Emotional Intelligence (Ei) and Educational Outcomesmentioning
confidence: 99%
“…Regarding the importance of social competence, Mavroveli et al, (2007) found that trait emotional self-efficacy is in fact related to social skills, and social status is a predictor of internalized disorders (Merrell & Gimpel, 1998). Studies on the benefits of emotion regulation on social competence have been fairly consistent; emotional intelligence can be directly linked to prosocial behavior (Dishion & Connell, 2006;Mavroveli et al, 2007). As a result, emotional intelligence practice can be implemented in institutions and settings where most social interactions take place -schools, workplaces, etc.…”
Section: Resultsmentioning
confidence: 99%
“…In a sample of Dutch adolescents, Mavroveli et al, (2007) found that students considered those peers who scored higher on emotional intelligence more cooperative. Trait emotional intelligence is associated with prosocial behavior and social competence, particularly important because knowing how to regulate one's emotions acts as a reference for determining the feelings and emotions of others.…”
Section: Emotion Regulation and Social Competencementioning
confidence: 97%
See 1 more Smart Citation
“…The investigators' purpose was to improve EI skills of the patients with a twelve week emotion intelligence workshop, as it has been already established that high EI is positively correlated with well-being, quality of life and improvements of their anxiety and burnout levels. In other words, patients with high EI seem to be less vulnerable to psychological disorders, as compared with patients with low EI levels (Mavroveli et al, 2007). It has been shown that people with high levels of EI can manage their emotions more effectively, can be more successful at solving emotional problems and managing stress, and can as a result be more productive and positive in their family and social relations (Matthews, Zeidner, 2000).…”
Section: Emotions and Diabetes Mellitusmentioning
confidence: 99%